Performance Analysis of Red Chilli in a Hybrid Collector with Solar Dryer - et. al., E Murali, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This article performed various analysis on Red chilli by hybrid collector with solar dryer (HCSD). This study was carried out forced convection solar dryer which performed better in all aspects such as drying time, moisture removal rate, electrical efficiency, electrical thermal efficiency, thermal efficiency and overall thermal efficiency. In general, solar radiation was provided a sources of generating energy to drive a solar dryer. Hybrid collector has been provided the electrical and thermal energy to run a solar dryer. The solar dryer was tested by drying 12 kg of red chilli in the drying air temperature in the range of 32 0C – 56 0C. The initial moisture content of the red chilli was 71.5 % (weight basis) and was reduced to the final moisture content of 16.2 % (weight basis) in 6 consistent days with clear sunny days. The HCSD was operated between 9 hrs to 16 hrs. Finally, comparative study was also handled for better understanding in HCSD, in which solar dryer drying made better outcome than open sun drying.